Immunization Tour: Preparing for Mass Immunization through Pharmacy and Nursing Interprofessional Student-led Service-learning - Jean Moon; Jeanne Pfeiffer; Jehad Adwan; Maria Rudie; Don Uden (University of Minnesota Libraries Publishing, 2014)
Pharmacy and nursing students piloted a collaborative student initiative to administer mass influenza immunizations to a large university campus. Through the support of the School of Nursing, College of Pharmacy, and University Health Service this project later turned into a unique service-learning interprofessional one credit elective course promoting public health philosophy and principles, emergency preparedness strategies, clinical skills, and interprofessional team competencies centered around influenza immunizations. Including lessons learned, this article will describe the evolution of this innovative student-led project.   Type: Case Study